2014
DOI: 10.1111/hel.12174
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of Indoleamine 2,3‐Dioxygenase in Helicobacter pylori‐Infected Human Gastric Mucosa Modulates Th1/Th2 Pathway and Interleukin 17 Production

Abstract: In H. pylori-infected human gastric mucosa, an enhanced expression of IDO is capable of modulating Th1/Th2 and Th17 pathways. This mechanism lowers gastric inflammation, possibly contributing to the persistence of H. pylori. Targeting the IDO pathway may be a new strategy for modulating H. pylori-induced mucosal immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Very recent data from analyses performed on gastric biopsy samples from human patients suggest an immune-modulatory and protective action of IDO1 against gastritis in H. pylori subjects [478]. This study reported elevated IDO1 expression in H. pylori-infected, but not uninfected, samples that inversely correlates with the severity of gastritis.…”
Section: Micro-organism Induction Of Ido1 In Vivosupporting
confidence: 46%
See 1 more Smart Citation
“…Very recent data from analyses performed on gastric biopsy samples from human patients suggest an immune-modulatory and protective action of IDO1 against gastritis in H. pylori subjects [478]. This study reported elevated IDO1 expression in H. pylori-infected, but not uninfected, samples that inversely correlates with the severity of gastritis.…”
Section: Micro-organism Induction Of Ido1 In Vivosupporting
confidence: 46%
“…Moreover, ex vivo inhibition of IDO1 in gastric biopsy cultures with 1-L-MT resulted in the increased expression of Th1-type markers of inflammation (i.e. IFNγ , Tbet and IL-17) and a reduced Th2 marker (IL-4), supporting an antiinflammatory action of IDO1 [478].…”
Section: Micro-organism Induction Of Ido1 In Vivomentioning
confidence: 79%
“…This mechanism lowers gastric inflammation, possibly contributing to the persistence of HP. 24 Chen and Blaser 25 suggest that the intensity of the response of the host against especially aggressive HP strands (with the cagA gene) might alter the pattern of Th1/Th2 immune response with the subsequent induction of immunoregulating lymphocytes that may prevent immune hyper-reactivity responses, such as asthma or allergy in cases where the Th2 pattern is predominant. It is very well known that intensity of TBI and chemotherapy used during conditioning dictate the integrity of the gastrointestinal mucosa and the subsequent transfer of bacterial lipopolysaccharide and other 'danger/pathogen-associated molecular patterns' (DAMPS/PAMPS) into the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…One such anti-inflammatory factor is indoleamine 2,3 dioxygenase (IDO) which depletes tryptophan (an essential amino acid for the host) in the environment. Larussa et al [16] report that IDO expression was enhanced in gastric biopsies from H. pylori infected compared with uninfected individuals. This would indicate that immune cells would be affected by the tryptophan deficiency, and indeed, the study also found that the levels of IDO expression correlated inversely with the gastritis score in H. pylori-infected gastric mucosa, but not in uninfected mucosa.…”
Section: Adaptive Immune Responses To H Pylori Infectionmentioning
confidence: 99%